EXPLORING THE OBESITY PREVALENCE AMONG TAIWANESE ADULTS FROM 2017 TO 2020: A STUDY ON ECONOMIC INCOME AND EDUCATIONAL ATTAINMENT - Chen, Hung-Chi; Chiang, Hsiang-Tsai (PEOPLE: International Journal of Social Sciences, 2024)
Purpose Existing research suggests that the prevalence of obesity varies by income and educational level, but patterns of income across different countries and regions may differ. Therefore, this study investigates the obesity prevalence among adults in Taiwan based on economic income and educational attainment, and identifies gender differences. Methods A total of 3481 adult males and 3510 adult females participated in the National Nutrition and Health Survey (years 2017-2020), providing data including height, weight, body fat percentage, education level, and income. Multivariate logistic regression analysis was used to analyse adjusted body mass index (BMI) and body fat percentage based on income and education level, as well as the relationship between income, education, and overweight/obesity. Results In males, there was a significant interaction between income and weight standard (Trend, p <0.05) and obesity (Trend, p <0.05). Compared to the lowest income group, the adjusted odds ratios (ORs) (95% confidence intervals) for overweight and obesity were 1.45 (0.09, 2.12) and 1.25 (0.82 to 1.76) respectively, for the highest income group. However, in the fully adjusted model for females, the association between income and overweight/obesity was not significant, but there was an inverse trend between education level and obesity. Discussion Education level and income have a certain impact on the obesity prevalence among adults in Taiwan, with differences observed between genders in the prevalence of obesity.